Public Sector Human Resource Management for Enhancing Tourism Services in the Mount Bromo Tourism Area (A Case Study at the Tourism and Culture Office of Probolinggo Regency) - Septiandika, Verto; Fitrianti, Deistiara (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The tourism potential of the Mount Bromo Area is not yet optimally supported by the quality of public services, where the Tourism and Culture Office of Probolinggo Regency, as the leading sector, faces significant challenges in the human resource capacity of its apparatus. This study aims to analyze the implementation of Public Sector Human Resource Management to improve service quality at the destination using a qualitative case study approach through in-depth interviews with 10 key informants, field observations, and document studies, with data analyzed interactively and validated through source triangulation. The findings reveal that HRM practices remain fragmented and administrative, lacking strategic integration, while the analysis of the five dimensions of service quality (Tangibility, Reliability, Responsiveness, Assurance, Empathy) shows uneven performance, with Reliability and Responsiveness being the main weak points. Furthermore, the planning, competency development, and performance appraisal systems are not yet aligned with the contextual needs of managing a super-priority destination. Therefore, service improvement requires a holistic approach through specific recommendations, including the development of a Strategic Competency Map, the transformation of capacity-building programs toward continuous learning, and a revolution in the performance appraisal system by integrating Key Performance Indicators (KPIs) based on service outcomes and tourist satisfaction.